2010
DOI: 10.1111/j.1365-2966.2009.16077.x
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar disc, envelope and bipolar outflow of the massive young stellar object W33A

Abstract: The young stellar object (YSO) W33A is one of the best known examples of a massive star still in the process of forming. Here we present Gemini North Altitude conjugate Adaptive optics for the Infrared (ALTAIR)/Near‐Infrared Integral Field Spectrograph laser‐guide star adaptive‐optics assisted K‐band integral‐field spectroscopy of W33A and its inner reflection nebula. In our data, we make the first detections of a rotationally flattened outer envelope and fast bipolar jet of a massive YSO at near‐infrared wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 24 publications
11
109
0
2
Order By: Relevance
“…The CO bandheads in emission are usually believed to originate in the inner gaseous disc (see e.g. Carr et al 1993;Antoniucci et al 2008), and have been observed in YSOs that display strong jets and Herbig-Haro (HH) objects (see, e.g., Davis et al 2011), whereas the CO bandheads in absorption may originate in cooler regions, like the YSO envelope (Davies et al 2010) or the photosphere of cool YSOs (see e.g. Rayner et al 2009).…”
Section: Optical and Nir Spectramentioning
confidence: 99%
“…The CO bandheads in emission are usually believed to originate in the inner gaseous disc (see e.g. Carr et al 1993;Antoniucci et al 2008), and have been observed in YSOs that display strong jets and Herbig-Haro (HH) objects (see, e.g., Davis et al 2011), whereas the CO bandheads in absorption may originate in cooler regions, like the YSO envelope (Davies et al 2010) or the photosphere of cool YSOs (see e.g. Rayner et al 2009).…”
Section: Optical and Nir Spectramentioning
confidence: 99%
“…This lends support to 145 • position angle to be the actual orientation of the system. The high-angular resolution IFU images presented in Davies et al (2010) have contributions from shocked H 2 emission as traced by extended 4.5 μm emission in Spitzer IRAC images (Cyganowski et al 2008). …”
Section: The Molecular Outflow and Near-ir Reflection Nebulamentioning
confidence: 99%
“…In Davies et al (2010), spectro-astrometry of the Brγ transition is also used to show that the near-IR source is at the base of the bipolar outflow on scales of 200 μ-arcseconds. The near-IR source most likely corresponds to the central object in W33A, as was assumed during the execution of the MIDI observations.…”
Section: The Molecular Outflow and Near-ir Reflection Nebulamentioning
confidence: 99%
“…Spectroscopic observations have also provided important kinematical evidence of accretion disks (see, e.g., Chandler et al 1995;Bik & Thi 2004;Wheelwright et al 2010;Davies et al 2010). These studies have greatly advanced our understanding of the physics of young stellar objects (YSOs), how the young stars gain their final mass, how the circumstellar matter, in which…”
Section: Introductionmentioning
confidence: 99%